Implementation of Syari'ah Economic Principles on the Management of Syari'ah Mutual Fund in Indonesia - Nunung Rodliyah; Risti Dwi Ramasari (Universitas Airlangga, 2018)
Syari’ah Financial Institution is one of the institutions of Islamic doctrine that is currently mushrooming in the midst of modern Indonesian society. Along with the growth of syari'ah financial institutions, MUI issued that interest is usury which is unlawful. The entry of syari'ah financial institutions in Indonesia made a new breakthrough in the syari'ah capital market. One of the products of syari'ah capital market is Syari'ah Mutual Fund. Syari'ah mutual funds are defined as mutual funds as referred to in the Capital Market Law and its implementing regulations whose management does not conflict with the principles of syari'ah in the capital market. The problem of this research is how is the interpretation of the regulation of syari'ah economic principle in Indonesia and how is the management of Syari'ah Mutual Funds based on syari'ah economic principle in Indonesia. This research is normative research with descriptive research type. The approach used is normative juridical. The data collection was done by literature study and document study. The data used are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The collected data is then analyzed qualitatively. The findings of the research show that there are 3 (three) principles of syari'ah economy namely the principles of Tauhid, Justice, and Benefits. The regulation of syari'ah economic principles in Indonesia is regulated in the DSN-MUI and compilation of Islamic law. Basically syari'ah economic principles are in the field of Bank financial institutions and Non-Bank financial institutions. The arrangement of syari'ah economic principles, as well as regulated in law but also governed by Syar'i Law and Fiqh law through Ijtihad, by the method of Mashlahah Mursalah. Implementation of investments in Syari'ah Mutual Fund transaction mechanism in investing through Syari’ah Mutual Funds should pay attention to things that are not against the Islamic Syari'ah. Implementation of the transaction contract should not be contrary to the Islamic Syari'ah, whether prohibited because (1) Forbidden in addition to the substance, which contains tadlis, ihtikar, ba'i najasy, garar, and usury, as well (2) Because unauthorized, i.e. the order and conditions are not met, there ta'alluq, and there are two contracts in one transaction simultaneously. The idea of syari’ah economic principles recommends to the Syari’ah Banking Supervisory Board to make further regulation in the development of investing through Syari’ah Mutual Funds in Indonesia.